1975
DOI: 10.1097/00006842-197507000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Musculosketal Symptoms and Non-REM Sleep Disturbance in Patients with “Fibrositis Syndrome” and Healthy Subjects

Abstract: In sleep studies of (a) patients with the "fibrositis syndrome" and (b) healthy subjects undergoing stage 4 sleep deprivation, we observed in both groups the anomalous presence of alpha-rhythms in the non-rapid-eye-movement (NREM) sleep EEG. This phenomenon has been termed alpha-delta sleep. In the healthy subjects stage 4 deprivation was accompanied by the temporary appearance of muscoloskeletal and mood symptoms comparable to the symptoms seen chronically in the patients. It is suggested that the external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
3
18

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 761 publications
(142 citation statements)
references
References 14 publications
5
116
3
18
Order By: Relevance
“…Several researchers conducted PSG in order to explore physiological foundations of poor sleep quality in patients with fibromyalgia experience. 25,26 In their study, Drewes et al 27 discovered various changes 31 demonstrated in their study that sleep disorder, waking up unrefreshed and PSG changes, which occur in FMS, might also occur in patients with OSAS.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers conducted PSG in order to explore physiological foundations of poor sleep quality in patients with fibromyalgia experience. 25,26 In their study, Drewes et al 27 discovered various changes 31 demonstrated in their study that sleep disorder, waking up unrefreshed and PSG changes, which occur in FMS, might also occur in patients with OSAS.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with FMS, impairment of especially NREM stage of sleep is seen [24]. First, in the year 1975, PSG reports indicated the presence of alpha intrusions in NREM deep sleep in patients with FMS [25].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AHI of ≥5 events/h were diagnosed with OSAS. Based on their AHI scores, the patients were categorized into mild (AHI, 5-15), moderate (AHI, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and severe OSAS (AHI, >30) groups according to the AASM Task Force criteria [11]. Oxygen desaturation index (ODI) was defined as the total number of measurements of oxyhemoglobin desaturation of ≥4% within ≥10 s-<3 min from the baseline divided by the total sleep time.…”
Section: Psg Evaluationmentioning
confidence: 99%
“…Poor sleep may aggravate pain and may also contribute to disturbed sleep. There is a relationship, in fact, between poor sleep and pain, and sleep disturbances are important in the genesis of tender points (37,38). Loss of deeper phases of sleep (stages three and four) is characteristic of FM and leads to the loss of restorative feelings on awakening.…”
Section: Sleep Dysfunctionmentioning
confidence: 99%